Barks of Terminalia Species-A New Source of Oxalic Acid - Bhatia, Kuldip; Ayyar, K. S. (Indian Forester, 1980)
The paper describes the various important uses and methods of preparing oxalic acid. Merits of the method of making oxalic acid using Terminalia barks has been discussed. Some suggestions to make the industry viable and job oriented have been given.